2020
DOI: 10.1002/npr2.12153
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Health Workers and General Population During COVID‐19 in IRAN: A Cross‐Sectional Study

Abstract: Background The COVID‐19 outbreak has exerted a great deal of psychological pressure on Iranian health workers and the general population. The aim of this study was to determine the effect of pandemic on anxiety and depression in Iranian population. Methods An online cross‐sectional study was conducted for the general public and healthcare workers in Iran using a questionnaire comprised of demographic questions and Hospital Anxiety and Depression Scale. Chi‐square test and univariate and multivariate logistic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 41 publications
0
39
4
1
Order By: Relevance
“…A total of 159,194 healthcare providers from 23 different Asia countries were involved in this systematic review and meta-analysis. Almost half (n = 70) of the studies were conducted in China [ 8 , 11 , 23 90 ], followed by 15 studies in India [ 10 , 91 – 104 ], 11 studies in Turkey [ 105 115 ], 10 studies in Saudi Arabia [ 116 125 ], 6 studies in Pakistan [ 126 131 ], 4 studies in Indonesia [ 132 – 135 ] and Nepal [ 136 139 ] respectively, 3 studies in Malaysia [ 140 142 ], Singapore [ 143 145 ], Japan [ 146 148 ] and Iran [ 149 151 ] respectively with 2 studies in Oman [ 152 , 153 ], Jordan [ 154 , 155 ], Philippines [ 156 , 157 ] and Bangladesh [ 158 , 159 ] respectively. Besides, Korea [ 160 ], Qatar [ 161 ], and Iraq [ 162 ] which each had one study, there were also some multinational studies that were conducted, with 2 of them involving several countries in Asian Pacific [ 9 , 163 ] and another one involving both Egypt and Saudi Arabia [ 164 ] (Table A4 in S4 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 159,194 healthcare providers from 23 different Asia countries were involved in this systematic review and meta-analysis. Almost half (n = 70) of the studies were conducted in China [ 8 , 11 , 23 90 ], followed by 15 studies in India [ 10 , 91 – 104 ], 11 studies in Turkey [ 105 115 ], 10 studies in Saudi Arabia [ 116 125 ], 6 studies in Pakistan [ 126 131 ], 4 studies in Indonesia [ 132 – 135 ] and Nepal [ 136 139 ] respectively, 3 studies in Malaysia [ 140 142 ], Singapore [ 143 145 ], Japan [ 146 148 ] and Iran [ 149 151 ] respectively with 2 studies in Oman [ 152 , 153 ], Jordan [ 154 , 155 ], Philippines [ 156 , 157 ] and Bangladesh [ 158 , 159 ] respectively. Besides, Korea [ 160 ], Qatar [ 161 ], and Iraq [ 162 ] which each had one study, there were also some multinational studies that were conducted, with 2 of them involving several countries in Asian Pacific [ 9 , 163 ] and another one involving both Egypt and Saudi Arabia [ 164 ] (Table A4 in S4 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 27 , 29 33 , 35 , 36 , 38 41 , 45 52 , 56 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 117 , 120 , 123 , 124 , 127 , 129 133 , 137 , 138 , 140 , 141 , 143 146 , 149 , 151 154 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other consequences of this pandemic included job burnout, increased health costs and psychological distress (fear, anxiety, depression, stress, insomnia, denial, anger, etc.) (Hassannia et al., 2020; Vizheh et al, 2020). High‐risk situations plus constant contact with contaminated environments, inadequate PPEs, lack of contact with the family members, frustration, prejudice, loneliness and exhaustion have been blamed for increased mental health problems in HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were from Eastern Asia (n = 40)[8][9][10], South-eastern Asia (n = 5)[63][64][65][66][67], Southern Asia (n = 18)[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], Western Asia (n = 15)[4,17,[86][87][88][89][90][91][92][93][94][95][96][97][98] and combination of South-eastern and Southern Asia (n = 2)[99,100] (Supplementary TableS2). Studies from Eastern Asia came from China, Japan, and Korea.…”
mentioning
confidence: 99%